La publicisation des liens entre l’antibiorésistance et l’alimentation dans la presse nationale étatsunienne - Estera Badau (Communication)
Although the scientific community has long been aware of the problem posed by antibiotic-resistant bacteria, political recognition of the problem is a recent development. The author uses discourse analysis tools to look at media coverage of known links between antibiotic-resistant bacteria and food in the United States. This paper is part of a larger discussion in the field of pragmatics about how public problems are formulated. The corpus is made up of articles published in two top American newspapers with different political leanings, The New York Times and The Washington Post, between 1984 and 2016.